DEVELOPMENT OF HOTS-BASED QUESTIONS ON BIOLOGY LEARNING - Adi Hartono; Ashar Hasairin; Diky Setya Diningrat (Universitas Islam Negeri Sumatera Utara, 2022)
According to observations on the Lower-Level Organisms Taxonomy course, it showed that the questions used in the course have not been presented at the higher-order thinking skill (HOTS) level. HOTS-based questions are one of the assessments in the cognitive domain that function to train HOTS and solve complex problems well. Moreover, it can train critical thinking skills as one aspect of the skills needed in the 21st century. Therefore, this study aims to develop HOTS-based questions on Monera topic to improve students' critical thinking skills. The research was conducted from January to February 2022. Development was carried out using ADDIE approach. Data collection techniques were carried out through the questionnaires and validation instruments by expert validators. The data were analyzed in two ways, namely content validity and construct validity. The results showed that the validity of the questions by expert validators was categorized as very good. Meanwhile, empirical validity shows that there were 10 questions declared valid from a total of 20 questions. The results of reliability test were 0.780 valid with a high interpretation. The test of difficulty level results showed that there were 8 moderate questions and 2 difficult questions. The results of differentiating power test showed that there were 1 very good question, 6 good questions, 2 sufficient questions and 1 weak question. Thus, it can be concluded that from a total of 20 HOTS-based questions that were developed only 10 questions were declared empirically feasible to improve students' critical thinking skills on Monera topic. It is recommended to use these questions in Lower-Level Organisms Taxonomy lectures.